Community Empowerment Through Training in Making Nutrition-Rich Food Menu for Stunting Toddlers in Sukoreno Village, Kalisat District : Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan Menu Makanan Kaya Gizi untuk Balita Stunting di Desa Sukoreno Kecamatan Kalisat (AgroNurse Kesehatan : Jurnal Pengabdian Masyarakat, 2023)
Stunting is still a problem that cannot be solved. The increase in stunting cases is the focus of problems in the indicators of the Sustainable Development Goals (SDGs). The problem of stunting can be suppressed with a good understanding of the community, especially parents, regarding the nutritional needs of children. The incidence of stunting due to malnutrition, recurrent infections, and lack of care through stimuli given to children in the golden period or the first 1000 days from conception to the age of two is something every parent needs to understand. The purpose of this community service is to be able to increase the community's knowledge and skills about the importance of nutrition in children through training in making nutrient-rich menus for toddlers. The training for making a menu rich in nutrition will be carried out in Kalisat District. The success of the dedication was obtained by an increase in partner knowledge as much as 90% of partners who actively asked questions during the discussion process and increased partners' skills in processing nutrient-rich dishes for toddlers.